Status of Local Service Delivery by the Local Government in Nepal (Nepalese Journal of Management Research, 2021)
The main focus of this study is to assess the status of local service delivery by the local government in Nepal. It has used descriptive and analytical research design. It focuses on the service delivered by local government. Service delivery of rural roads/bridges; livestock services; basic health services; primary education; small irrigation; and agriculture extension were found to be good, whereas the level of implementation of the sectoral functions of local government in community water supply and sanitation was found to be weak as per the collected data. The findings from this study can provide information about the status of services delivered by the local government in Nepal. It can be helpful to provide some special guidelines to the policy makers for improving local governance.